The Role of e-WOM and Consumer Experience on Repurchase Intention and Sustainability Mediated by Consumer Satisfaction Among Fixed Broadband Internet Users - Riyanto, Dedi; Indrajaya, Sonny (Dinasti Publisher, 2025)
The purpose of this research is to examine Sustainable Development Goal (SDG) 11 on sustainable cities and communities by identifying factors influencing Fixed Broadband Internet users in Jakarta. This quantitative study, with an unknown population, surveyed 222 respondents using a Likert-scale questionnaire (1-5). Hypothesis testing was conducted using the Structural Equation Model (SEM) with Smart PLS. The results indicate that e-WOM significantly affects Consumer Satisfaction, Consumer Experience significantly affects Consumer Satisfaction, e-WOM significantly affects Repurchase Intention, Consumer Experience significantly affects Repurchase Intention and Sustainability, and Consumer Experience influences Repurchase Intention through Consumer Satisfaction as a mediator. Additionally, Customer Satisfaction significantly affects Repurchase Intention, which in turn influences Sustainability.